Pendidikan Islam Di Era Sains Dan Teknologi Modern - Kartini K (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
This research aims to analyze the strategic role of Islamic education in facing and directing the rapid development of modern science and technology (IPTEK). Advances in science and technology, while bringing convenience and innovation, often raise moral and ethical challenges due to materialistic and secularist paradigms. Islamic education serves as a guiding and supervising partner, emphasizing the values of monotheism and sharia as the primary standards for the development and utilization of IPTEK. This research method uses a qualitative-descriptive approach with a literature review. The results indicate that Islamic education must holistically integrate religious knowledge and general knowledge (science) through curriculum adjustments and learning methodologies. Key strategies include making Islamic Aqeedah the basis for IPTEK development and Islamic Sharia as the ethical standard for its utilization. Furthermore, it is necessary to improve the digital competence of educators and instill digital literacy based on Islamic ethics in students to counteract the negative impacts of technology. In conclusion, Islamic education plays a vital role in producing a generation of Muslim scientists who are scientifically competent (mastering IPTEK) while remaining steadfast in religious and moral values (having noble character), so that IPTEK can function as a means to achieve the welfare of the community.